STUDY OF THE FUNCTIONAL STATE OF THE CARDIORESPIRATORY SYSTEM IN STUDENT-ATHLETES - Sagatov, Husniddin (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
STUDY OF THE FUNCTIONAL STATE OF THE CARDIORESPIRATORY SYSTEM IN STUDENT-ATHLETES